Effectiveness of Personal Protective Equipment in Reducing Skin Exposure to Soluble Platinum - Linde, Stephanus J L; Franken, Anja; du Plessis, Johannes L (Annals of work exposures and health, 2021)
Various forms of personal protective equipment (PPE), including disposable coveralls and gloves, are used to help reduce skin exposure to soluble platinum in precious metals refineries. We aimed to investigate the effectiveness of PPE in reducing workers' skin exposure to soluble platinum. Thirty precious metals refinery workers were divided into two groups according to their use of PPE and related procedures. Group A (n = 13) used disposable coveralls worn over standard overalls along with long-sleeved rubber gloves, while Group B (n = 17) used standard overalls only and surgical nitrile gloves. The skin (palm, wrist, neck, and forehead) and respiratory exposure of these groups to soluble platinum were concurrently measured (using Ghostwipes™ and MDHS 46/2, respectively) along with their urinary platinum excretion. Both groups of workers experienced comparable geometric mean (GM) respiratory exposure to soluble platinum (Group A = 0.744 µg m-3 versus Group B = 0.711 µg m-3) (P = 0.789), but significantly lower skin exposure (average of all measured anatomical areas) was found for Group A (Group A = 0.005 µg cm-2 versus Group B = 0.033 µg cm-2) (P = 0.018). Significantly lower skin exposure was measured on the palm (P = 0.017), wrist (P = 0.017), forehead (P = 0.027) of Group A workers compared with Group B. No significant difference was found for the urinary platinum excretion of the two groups (Group A GM = 0.208 µg g-1 creatinine versus Group B GM = 0.361 µg g-1 creatinine) (P = 0.273). The use of disposable coveralls and long-sleeved rubber gloves, along with strict usage procedures, proved effective in reducing precious metals refinery workers' skin exposure to soluble platinum.